2000
DOI: 10.2134/agronj2000.923472x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen on Productivity and Nutritive Value of Forage Chicory

Abstract: Chicory (Cichorium intybus L.) is highly productive and responsive to N fertilization under midsummer conditions in the eastern USA. We conducted a field experiment for 3 yr on a Ramsey soil (loamy, siliceous, subactive, mesic Lithic Dystrudept) in southern West Virginia to determine if fertilizer N influenced forage chicory nutritive value and NO3–N concentration. Each N rate (0, 80, 160, 240, or 480 kg N ha−1) was replicated three times in a randomized block design. Swards were clipped at 6‐wk intervals duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 19 publications
(38 reference statements)
4
42
0
Order By: Relevance
“…1999). Early accumulation and gradual decline in NO 3 observed for Forage Feast, Lacerta and Grasslands Puna grown in glasshouse agrees with observations on field‐grown Grasslands Puna (Belesky and Ruckle 2000). Repeated defoliation altered shoot : root DM allocation, but did not appear to cause an increase in NO 3 as suggested by Vuylsteker et al.…”
Section: Nitrate Concentrationssupporting
confidence: 85%
See 1 more Smart Citation
“…1999). Early accumulation and gradual decline in NO 3 observed for Forage Feast, Lacerta and Grasslands Puna grown in glasshouse agrees with observations on field‐grown Grasslands Puna (Belesky and Ruckle 2000). Repeated defoliation altered shoot : root DM allocation, but did not appear to cause an increase in NO 3 as suggested by Vuylsteker et al.…”
Section: Nitrate Concentrationssupporting
confidence: 85%
“…The results suggest that N could improve the likelihood of chicory establishment where leaf number is considered a criterion for success (Sanderson and Elwinger 2000). Under field conditions, plant density as well as leaf appearance should be taken into consideration for stand persistence when high rates of N are applied (see Belesky and Ruckle 2000). The leaf appearance rate of Lacerta, prior to N application averaged 0.21 leaves plant −1 day −1 or about 10 leaves in a 50‐day growth interval.…”
Section: Leaf Appearancementioning
confidence: 99%
“…The observed CP content of chicory from both experiments was consistent and higher than that reported by Elgersma et al (2014) but in the lower range of values reported by others (Belesky et al, 2000;Labreveux et al, 2006;Kidane, 2010). The reasons could be that, at least, in other experiments the crop was adequately fertilized and it is also reported that the crop responds to (nitrogen) fertilization (Collins & McCoy, 1997;Belesky et al, 2000) with increased CP and DM yield.…”
Section: Chicory Growth Winter Survival and Chemical Compositionsupporting
confidence: 90%
“…The reasons could be that, at least, in other experiments the crop was adequately fertilized and it is also reported that the crop responds to (nitrogen) fertilization (Collins & McCoy, 1997;Belesky et al, 2000) with increased CP and DM yield. Furthermore, the botanical composition of chicory in our trial was about 52%, on DM basis, whilst the rest was accounted for by annual weeds which could have diluted the CP content of the chicory sward.…”
Section: Chicory Growth Winter Survival and Chemical Compositionmentioning
confidence: 99%
“…In New Zealand, up to 33% of Puna chicory plants died in the first year of grazing (10). West Virginia research demonstrated that the chicory component of mixed species pastures decreased from 80 to 20% of sward dry matter after 3 years of cutting management (3) and that high N fertilization rates (> 400 lb/acre) hastened stand decline (4). Nitrogen was applied at 150 lb/acre (in three applications of 50 lb/acre each) in the current study, thus N fertilization may not have contributed to stand decline.…”
Section: Persistence Of Chicorymentioning
confidence: 99%